Distribution by transmembrane potential of L929 cells in suspension before and after freezing - Gordiyenko, Olga; Smolyaninova, Yevgeniya; Poliakova, Hanna; Kovalenko, Svitlana; Kovalenko, Igor; Todrin, Oleksandr (Problems of Cryobiology and Cryomedicine, 2026)
Monitoring of cell membrane potential is an important tool for assessing their state during functioning, as well as under the influence of external factors. The distribution of transmembrane potential of L929 cells in cultured suspension and after freezing is determined in this work. It is shown that in the control suspension, cells are in different phases of the cell cycle: a larger fraction of cells (82%) is in a hyperpolarized state of varying degrees (G1 and S-phases), and only a small percentage of them (~7%) are in the division stage and have a low transmembrane potential value (depolarized cells). Freezing the L929 cell suspension in the standard mode (10% DMSO, cooling rate of 1 °C/min to –80 °C with subsequent immersion in liquid nitrogen) practically does not change the part of cells in the hyperpolarized state. At the same time, the fraction of cells in the depolarized state disappears. Obviously, cells that were in the division stage are more sensitive to cryodamage factors. Freezing a suspension of L929 cells with a reduced concentration of DMSO (5%) resulted in a signifi cant decrease in the part of cells in a hyperpolarized state and a signifi cant decrease in the ability of cells to adhere. Probl Cryobiol Cryomed. 2026; 36(2): 95—105